Age-related upregulation of dense core vesicles in the central inferior colliculus - Mellott, Jeffrey G.; Duncan, Syllissa; Busby, Justine; Almassri, Laila S.; Wawrzyniak, Alexa; Iafrate, Milena C.; Ohl, Andrew P.; Slabinski, Elizabeth A.; Beaver, Abigail M.; Albaba, Diana; Vega, Brenda; Mafi, Amir M.; et al. (Frontiers in Cellular Neuroscience, 2024)
Presbycusis is one of the most prevalent disabilities in aged populations of industrialized countries. As we age less excitation reaches the central auditory system from the periphery. To compensate, the central auditory system [e.g., the inferior colliculus (IC)], downregulates GABAergic inhibition to maintain homeostatic balance. However, the continued downregulation of GABA in the IC causes a disruption in temporal precision related to presbycusis. Many studies of age-related changes to neurotransmission in the IC have therefore focused on GABAergic systems. However, we have discovered that dense core vesicles (DCVs) are significantly upregulated with age in the IC. DCVs can carry neuropeptides, co-transmitters, neurotrophic factors, and proteins destined for the presynaptic zone to participate in synaptogenesis. We used immuno transmission electron microscopy across four age groups (3-month; 19-month; 24-month; and 28-month) of Fisher Brown Norway rats to examine the ultrastructure of DCVs in the IC. Tissue was stained post-embedding for GABA immunoreactivity. DCVs were characterized by diameter and by the neurochemical profile (GABAergic/non-GABAergic) of their location (bouton, axon, soma, and dendrite). Our data was collected across the dorsolateral to ventromedial axis of the central IC. After quantification, we had three primary findings. First, the age-related increase of DCVs occurred most robustly in non-GABAergic dendrites in the middle and low frequency regions of the central IC during middle age. Second, the likelihood of a bouton having more than one DCV increased with age. Lastly, although there was an age-related loss of terminals throughout the IC, the proportion of terminals that contained at least one DCV did not decline. We interpret this finding to mean that terminals carrying proteins packaged in DCVs are spared with age. Several recent studies have demonstrated a role for neuropeptides in the IC in defining cell types and regulating inhibitory and excitatory neurotransmission. Given the age-related increase of DCVs in the IC, it will be critical that future studies determine whether (1) specific neuropeptides are altered with age in the IC and (2) if these neuropeptides contribute to the loss of inhibition and/or increase of excitability that occurs during presbycusis and tinnitus.